Efficacy and Safety of Cetuximab Dosing (biweekly vs weekly) in Patients with KRAS Wild-type Metastatic Colorectal Cancer: A Meta-analysis. (19th February 2022) - Parikh, Aparna R; Gonzalez-Gugel, Elena; Smolyakova, Natalia; Jen, Min-Hua; Toms, Nikki; Lin, Yong; Kim, Jong Seok; Kopetz, Scott
Abstract : Cetuximab is an immunoglobulin G1 monoclonal antibody targeting and binding the EGFR expressed in cancer cells. Cetuximab 500 mg/m2 biweekly plus chemotherapy is commonly used and recommended by NCCN guidelines. This meta-analysis compares efficacy and safety between biweekly and weekly cetuximab. Abstract: Background: Cetuximab 500 mg/m 2 biweekly (Q2W) plus chemotherapy is commonly used and recommended by NCCN guidelines. This meta-analysis compares efficacy and safety between Q2W versus weekly (Q1W) cetuximab dosing. Methods: A systematic literature review was performed on Pubmed and RightFind (2007-2017) for patients with KRAS wild-type mCRC who received Q2W or Q1W cetuximab and other treatments. Observational studies and case reports were excluded. Randomized trials comparing Q2W and Q1W dosing, and single-arm trials with only Q2W schedule were included. CRYSTAL, a phase 3 randomized study with Q1W cetuximab dosing was paired with each single-arm study with a Q2W schedule and reweighted to achieve similar demographic/baseline characteristics. Overall survival (OS) and progression-free survival (PFS) with hazard ratios (HR), overall response rate (ORR) with odds ratios, and risk difference of adverse events of special interest (AESI) between Q2W versus Q1W cetuximab were analyzed. Results: Five phase 2 studies with cetuximab Q2W/Q1W dosing schedules were identified: CECOG (phase 2; Q2W, n = 77; Q1W, n = 75), NORDIC 7.5 (phase 2; Q2W, n = 152) and NORDIC 7 (arm C of phase 3; Q1W, n = 109), CELINE ( n = 60), OPTIMIX ( n = 99), and APEC ( n = 289) all phase 2, Q2W, single-arm studies paired with CRYSTAL Q1W dosing ( n = 303). Efficacy was similar between Q2W versus Q1W administration; OS HR = 0.96, 95% confidence interval (CI) [0.89, 1.04]; PFS HR = 0.96, 95% CI [0.87, 1.05]; ORR odds ratio 1.16, 95% CI [0.96, 1.41]. Mean differences (Q2W-Q1W) across AESI rates were not clinically meaningful with no obvious directionality. Conclusion: This meta-analysis demonstrated no significant differences in efficacy and safety between Q2W versus Q1W cetuximab administration in mCRC patients.